Pembelajaran Nahwu dengan Metode Demonstrasi sebagai Upaya Efektif Guru dalam Mencapai Tujuan Kegiatan Belajar Mengajar - Al Ghozali, M. Dzikrul Hakim; Hasan, A. Hamdan Zainul (ISLAMIKA, 2024)
The purpose of this study was to find out how the teacher's effective efforts in the learning of Nahwu with the demonstration method at Madrasah Diniyah Al Quran Bahrul Ulum Jombang. The main focus in this research includes three aspects: Effective efforts of teachers in using demonstration methods in learning Nahwu, supporting factors and limiting factors. The method used is qualitative research. This type of research is descriptive analysis research. Data analysis is used for collection, presentation, interviews and documentation. Data was validated through triangulation of sources. The results of the research conducted can show an increase in teacher efforts in effective Nahwu learning by using the demonstration method in compiling and understanding sentences or words in Arabic. The supporting factors for effective teacher efforts in learning Nahwu with demonstration methods to improve understanding of Nahwu are mastery of the material, having the ability to apply demonstration methods, and being able to work actively with students. The inhibiting factors are more focused on the limitations of teachers' understanding, lack of preparation to implement this method, and inability to provide feedback.